Organic carbon burial during OAE2 driven by changes in the locus of organic matter sulfurization - Morgan Reed Raven; David A. Fike; Maya L. Gomes; Samuel M. Webb; Alexander S. Bradley; Harry-Luke O. McClelland (Nature Communications, 2018)
The mechanisms responsible for the burial of vast quantities of organic matter during Ocean Anoxic Event remain unclear. Here, the authors combine biogeochemical analysis and modeling and show that sulfurization could play a critical role in facilitating globally elevated burial of organic matter.